Effect of elevated temperature on the durability and strength properties of concrete with ground rice husk ash as a partial replacement to cement: a review - Makinta, B.; Mohammed, K.; Ocholi, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Concrete is a construction material composed of cement, fine aggregates (sand) and coarse aggregates mixed with water which hardens with time. Cement is an important constituent in the concrete composite; however, its cost is relatively very high, this has impacted in the cost of concrete production and by extension on the cost of housing delivery in Nigeria. Rice husk ash is one of the promising pozzolanic materials that can be blended with Portland cement for the production of durable concrete and at the same time a value-added product. the use of the rice husk ash as partial replacement to cement in concrete not only improve the strength of concrete, protection against cracking, spalling, reduce density and porosity of the concrete. It also reduce the emission of carbon monoxide to the environment which is very dangerous to the atmosphere. The elevated temperature is one of the most harmful effects that cause durability problems in construction; this effect can cause permanent damage in construction and reduce the service life. This paper reviews the work presented by various researchers on effect of elevated temperature on the durability and strength properties of concrete using rice husk ash as partial replacement. From the available literature reviewed, there is a possible research gab in investigating the effect of elevated temperature on concrete with rice husk ash as partial replacement to cement, because most of the researchers have focused on conventional concrete, whereas concrete with rice husk ash as replacement to cement have been recommended for use with a replacement value of 10-20%. The degree of its performance of these recommended replacement needs to be investigated.